STUDY OF ANTHROPOMETRY AND ERGONOMICS OF DESK AND CHAIR DESIGN FOR ELEMENTARY SCHOOL (CASE STUDY: PUBLIC ELEMENTARY SCHOOL 008 PURNAMA) - Fitra Fitra; Azmi Azmi; Novri Jenita Marbun; Nur Arif Fathurrozi (Center for Study and Journal Management FTI UMI, 2020)
Desks and chairs are supporting facilities for learning activities at various school levels, especially elementary schools or mostly known as SD. The Government of Dumai City through the Education authorities provided desks and chairs for learning process. SD 008 Purnama is one of the schools that received desks and chairs as aid. However the desks and chairs provided are not ergonomic in terms of the size of desks and chairs compared to size of student’s body. Somehow the un-ergonomic desks and chairs generate uncomfortable during learning and teaching process. In order to have proper anthropometry data of student of SD 008 Purnama and to be recommended to determine the size of desks and chairs ergonomically is the main purpose of this study.This study discusses the ergonomics of the design of the desks and chairs in elementary schools by using anthropometric data of students in grade 1 and 6. The research method used is quantitative research using the anthropometric approach. This research was conducted at SD 008 Purnama so that it can be used as main reference for the size desks and chairs for All elementary schools in the city of Dumai.The results of this study were the recommended Desk and chair sizes based on anthropometric data of students at SD 008 Purnama. Anthropometric data obtained were the high of desk and chair which can be raised and lowered. The high of desk was obtained 42.40 cm-67.35 cm and chair 29.22 cm-42.94 cm. However also obtained the length of desk was 64,57 cm, width 59.02 cm, the high of desk surface from below was 37.72 cm, the length of chair was 43.16 cm, the width of seat base was 36.89 cm, chair back height was 38.55 cm, chair back width was 38.55 cm and the high of footrest for desk and chair was 7.17 cm